2000
DOI: 10.1073/pnas.160266497
|View full text |Cite
|
Sign up to set email alerts
|

Learning about pain: The neural substrate of the prediction error for aversive events

Abstract: Associative learning is thought to depend on detecting mismatches between actual and expected experiences. With functional magnetic resonance imaging (FMRI), we studied brain activity during different types of mismatch in a paradigm where contrastingcolored lights signaled the delivery of painful heat, nonpainful warmth, or no stimulation. When painful heat stimulation was unexpected, there was increased FMRI signal intensity in areas of the hippocampus, superior frontal gyrus, cerebellum, and superior parieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
143
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(167 citation statements)
references
References 44 publications
20
143
2
2
Order By: Relevance
“…Thus, long-term potentiation (LTP) is present in the vermis after fear learning which is strictly related to associative processes, since it is not present following unpaired CS and US presentation. This conclusion is in line with the behavioral studies showing the requirement of the vermis for CS-US association, but not for baseline responses to CS and US , Ploghaus et al 1999, Ploghaus et al 2000and Maschke et al 2002. Synaptic changes were localized to vermal lobules V and VI, an area that receives convergence of acoustic and nociceptive stimuli Stowell 1944 andSaab andWillis 2003) and it is related to the expression of emotional behavior Sebastiani et al 1992).…”
Section: Neural Basis Of the Cerebellar Involvement In Learned Fearsupporting
confidence: 86%
See 2 more Smart Citations
“…Thus, long-term potentiation (LTP) is present in the vermis after fear learning which is strictly related to associative processes, since it is not present following unpaired CS and US presentation. This conclusion is in line with the behavioral studies showing the requirement of the vermis for CS-US association, but not for baseline responses to CS and US , Ploghaus et al 1999, Ploghaus et al 2000and Maschke et al 2002. Synaptic changes were localized to vermal lobules V and VI, an area that receives convergence of acoustic and nociceptive stimuli Stowell 1944 andSaab andWillis 2003) and it is related to the expression of emotional behavior Sebastiani et al 1992).…”
Section: Neural Basis Of the Cerebellar Involvement In Learned Fearsupporting
confidence: 86%
“…2) while a sensory cue that anticipates the painful stimulation leads to activation of posterior cerebellar vermis ( Fig. 2A) (Ploghaus et al 1999 andPloghaus et al 2000). Therefore, nearby but separate regions are engaged during fear experience and associative learning, i.e.…”
Section: Human Cerebellum and Fear Memoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The hippocampus, on the other hand, has been associated with novelty detection during acute painful stimulation (Bingel et al, 2002;Schneider et al, 2001). Hippocampal activity was reduced when attention was directed away from the painful stimulus (Ploghaus et al, 2000), and it was most consistently observed in studies in …”
Section: Discussionmentioning
confidence: 77%
“…For instance, Wills et al (2007) found differences in the event-related potentials evoked by the onset of stimuli which had previously been either uniquely predictive of a surprising outcome or completely redundant to the occurrence of an expected outcome. Using functional magnetic resonance imaging (fMRI), Ploghaus et al (2000;see also O'Doherty, Dayan, Friston, Critchley, & Dolan, 2003;Turner et al 2004) also found neural substrates that appeared to code absolute prediction error, that is, the mismatch between expected outcome and actual outcome regardless of whether that outcome is overpredicted or underpredicted. On the whole, these studies provide evidence of changes in stimulus processing dictated, in some fashion, by the association between CS and US.…”
Section: Learning and Attentional Changementioning
confidence: 99%